On energy harvesting form time-limited excitations: simulations and case study - Gatti, G.; Brennan, M. J. [UNESP]; Tehrani, M. G. (Katholieke Univ Leuven, Dept Werktuigkunde, 2014)
Linear resonant harvesters have been the most common type of generators used to scavenge energy from mechanical vibrations. When subject to harmonic excitation, good performance is achieved once the device is tuned so that its natural frequency coincides with the excitation frequency. In such a situation, the average power harvested in a cycle is proportional to the cube of the excitation frequency and inversely proportional to the suspension damping, which is sought to be very low. However, a very low damping involves a relatively long transient in the system response, where the classical formulation adopted for steady-state regimes do not hold. This paper presents an investigation into the design of a linear resonant harvester to scavenge energy from time-limited harmonic excitations involving a transient response, which could be more likely in some practical situations. An application is presented considering train-induced vibrations.